Praktik Kawin Paksa Di Desa Ulaweng Riaja Kecamatan Amali Kabupaten Bone - Marnawati Marnawati; Darmawati Darmawati; Asrul Muslim (SOSIORELIGIUS, 2020)
Marriage is the executor of human nature processes not only based on biological needs between men and women that are considered valid. In Islamic marriage law contains elements of a psychiatric and spiritual nature covering the life of the inner being, humanity and truth. Marriage is necessary to form a happy and prosperous family. But the reality is not so. Where a child is forced to marry by a parent without the consent of either party. Marriages that occur due to insistence or pressure are difficult to realize a harmonious family.  The results showed that the factors that cause forced marriage that occurred in the village of Ulaweng Riaja Amali subdistrict include: Strengthening family relationships, the existence of habits of matchmaking, factors of noble descent, the stigma of women who do not practice, the lack of knowledge of parents. The impacts are negative impacts such as domestic violence, parents interfering in the child's household, psychological disorders, inharmonious domestic life, and leading to divorce.